AUTHENTIC ASSESSMENT PRACTICES OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN CAMARINES NORTE: IMPLICATIONS FOR TEACHER PROFESSIONAL DEVELOPMENT - Jethro T. Ramirez (World Journal of Advanced Research and Reviews, 2026)
This study examined the authentic assessment practices of public elementary school teachers in the First Congressional District of the Schools Division Office of Camarines Norte. Specifically, it investigated the extent to which teachers implemented performance task assessment, outcome-based assessment, and portfolio assessment, identified challenges encountered in implementation, and determined differences in practices and challenges when grouped according to selected profile variables. A descriptive research design was employed involving 320 public elementary school teachers selected through proportionate stratified random sampling. Data were gathered using a researcher-developed and validated questionnaire. Descriptive statistics, Kruskal-Wallis H Test, and Mann-Whitney U Test were utilized in analyzing the data. Findings revealed that teachers highly practiced authentic assessment across all dimensions. Performance Task Assessment and Outcome-Based Assessment both obtained a grand mean of 4.30, while Portfolio Assessment registered a grand mean of 4.21. Challenges in implementation were fairly encountered (M = 3.37), with time constraints, inadequate resources, and insufficient training emerging as the most commonly reported concerns. Significant differences were observed in Performance Task Assessment when respondents were grouped according to position and in Outcome-Based Assessment when grouped according to sex. No significant differences were found in the challenges encountered when respondents were grouped according to age, sex, position, or years of teaching experience. The study concludes that authentic assessment has become an established classroom practice among elementary school teachers; however, sustained professional development and institutional support remain necessary to strengthen implementation. A training program, Project REAL Assessment, is proposed to address identified needs.